THE ECONOMIC ESSENCE OF THE REPORT ON THE FINANCIAL CONDITION OF COMMERCIAL BANKS AND ISSUES OF ITS IMPROVEMENT: https://doi.org/10.5281/zenodo.13944496 - Uralov , Hojiakbar (Science technology&Digital finance, 2024)
This article covers the economic essence of the report on the financial condition of commercial banks and the theoretical foundations and practical methodologies of its improvement, various methods of analysis, the peculiarities of using horizontal and vertical methods of analysis of financial reporting indicators in a wide range.